Degradation of Reading Interest Due to The Influence of Gadgets on Elementary School Students: Degradasi Minat Baca Akibat Pengaruh Gadget Pada Siswa Sekolah Dasar - Khosiah, Nur; Zainab, Siti; Andriani, Silvi (Madrosatuna: Journal of Islamic Elementary School, 2024)
The rapid development of technology can have many positive and negative influences on human life, especially in the field of education. This is shown by the presence of gadgets. Gadgets are technology that can be accessed by all groups, from children, teenagers, adults and even the elderly. Excessive use of gadgets can cause addiction and even have a negative impact on children's education. Where children prefer to spend their time playing with gadgets and often neglect their education. Children tend to focus more on gadgets than reading a book, this can reduce children's interest in reading. Thus, the importance of children's awareness of their interest in reading really needs to be emphasized so that children's knowledge increases. The aim of this research is to determine the impact of gadgets on the degradation of elementary school students' reading interest.